Clinical and genetic characterization of AP4B1‐associated SPG47. Issue 2 (28th November 2017) - Ebrahimi‐Fakhari, Darius; Cheng, Chi; Dies, Kira; Diplock, Amelia; Pier, Danielle B.; Ryan, Conor S.; Lanpher, Brendan C.; Hirst, Jennifer; Chung, Wendy K.; Sahin, Mustafa; Rosser, Elisabeth; Darras, Basil; et al.
Abstract : The hereditary spastic paraplegias (HSPs) are a heterogeneous group of disorders characterized by degeneration of the corticospinal and spinocerebellar tracts leading to progressive spasticity. One subtype, spastic paraplegia type 47 (SPG47 or HSP‐ AP4B1 ), is due to bi‐allelic loss‐of‐function mutations in the AP4B1 gene. AP4B1 is a subunit of the adapter protein complex 4 (AP‐4), a heterotetrameric protein complex that regulates the transport of membrane proteins. Since 2011, 11 individuals from six families with AP4B1 mutations have been reported, nine of whom had homozygous mutations and were from consanguineous families. Here we report eight patients with AP4B1 ‐associated SPG47, the majority born to non‐consanguineous parents and carrying compound heterozygous mutations. Core clinical features in this cohort and previously published patients include neonatal hypotonia that progresses to spasticity, early onset developmental delay with prominent motor delay and severely impaired or absent speech development, episodes of stereotypic laughter, seizures including frequent febrile seizures, thinning of the corpus callosum, and delayed myelination/white matter loss. Given that some of the features of AP‐4 deficiency overlap with those of cerebral palsy, and the discovery of the disorder in non‐consanguineous populations, we believe that AP‐4 deficiency may be more common than previously appreciated.